RECORD OF A RUDIST FROM PELAGIC BASINAL LIMESTONES (UPPER CRETACEOUS, LESSINI MOUNTAINS, NORTHERN ITALY) - RICCARDO CESTARI; ENRICO TREVISANI; GUIDO ROGHI (Rivista Italiana di Paleontologia e Stratigrafia, 2013)
The mid-Cretaceous succession of the central Southern Alps (Trento and Verona) is mainly represented by basinal deposits of the Scaglia Variegata.In this paper, the presence of a Radiolitidae in the Scaglia Variegata of the Lessini Mountains is reported. It is the first finding of a well preserved rudist, which belongs to the Radiolitidae (Sauvagesia sp.) family. The specimen was found in Cenomanian basinal biomicrites.